ALANKARAS IN RATNAVALI - Raghavan, Sujatha (International Journal of Research -GRANTHAALAYAH, 2016)
RATNAVALI Drama was written by SRI HARSHA a famous poet in Sanskrit. It contains four acts. Udayana is the courages Hero and Rarnavali is heroine in this drama. The main sentiment in this drama is SRINGARA, and main Virtham is KOWSIKI. Here the author describes the love between Udayana and Ratnavali in heart touching and beautiful manner. Many types of Alankaras used for this purpose which was taken from Kuvalayananda.